Teknik Cognitive Restructuring Untuk Meningkatkan Sikap Optimisme - Khairat, Imalatul; Mudrikah, Syifa (Universitas Mathla'ul Anwar Banten, 2022)
An optimistic attitude makes the individual able to move without hesitation in each of his activities. And teenagers are expected to have an optimistic attitude so that they are able to actualize themselves. This study was conducted to analyze the differences in optimism attitudes of late adolescents before and after being given group guidance services with cognitive restructuring techniques, using the quantified research method of one group pretest posttest design type experiment. The sample used in this study was 8 late adolescents. The data collection techniques used in this study were questionnaires related to optimism attitudes compiled by the researchers themselves, and data analysis techniques using the wilcoxon signed rank test. The results of this study showed an increase in the optimistic attitudes of late adolescents after obtaining group guidance services with cognitive restructuring techniques. The conclusion of this study is that cognitive restructuring techniques are effective in improving attitudes of optimism in late adolescence.